ABO/Rh Blood Groups and the Temperament (Mizaj) Based on Traditional Persian Medicine Perspective: A Cross-sectional Study: - Parvizi, Mohammad Mahdi; Molayemat, Mohadeseh; Rezaee , Maryam; Shirazi Yeganeh, Babak; Rampp, Thomas; Hashempur, Mohammad Hashem (Galen Medical Journal, 2023)
Background: Mizaj is a fundamental concept in traditional Persian medicine (TPM) that explains the physiological and psychological traits of human beings. This study aimed to investigate the association between the ABO/Rh blood groups and the Mizaj. Materials and Methods: This cross-sectional study was conducted on 18-60 years old individuals who visited the Iranian Blood Transfusion Organization, Shiraz Branch. We used Mojahedi’s Mizaj questionnaire to determine the Mizaj of the participants. The participants’ blood group and Rh were determined based on the antibodies against types A, B, and Rh antigens of their blood. Results: We assessed 308 individuals consisting of 174 (56.49%) male and 134 (43.51%) female. The results of our study showed a significant relationship between the AB blood group and the cold Mizaj in both simple and compound Mizaj categories (P=0.012, P=0.014, respectively). Logistic regression analysis revealed that people with the AB blood group were 2.88 times more likely to have cold Mizaj than people with the O blood group (OR=2.88, 95% CI: 1.16 to 7.15). In addition, those with the A blood group were found to be 54% less likely to have a dry Mizaj than those with the O blood group (OR=0.46, 95% CI: 0.23 to 0.92). There was no significant association between the participants’ Mizaj and their Rh blood group (P>0.05). Conclusion: It seems that there was a significant relation between the AB blood group and cold Mizaj, as well as the A blood group and dry Mizaj. However, further studies are recommended with controlling the probable confounding factors.